2009
DOI: 10.1111/j.1467-8578.2009.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

RESEARCH SECTION: Nurture groups: a large‐scale, controlled study of effects on development and academic attainment

Abstract: Nurture groups have contributed to inclusive practices in primary schools in the UK for some time now and have frequently been the subject of articles in this journal. This large-scale, controlled study of nurture groups across 32 schools in the City of Glasgow provides further evidence for their effectiveness in addressing the emotional development and behaviour problems of vulnerable children. In particular, Sue Reynolds, Principal Educational Psychologist, Maura Kearney, Senior Educational Psychologist, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…There is now a sizeable evidence base that indicates that primary school Nurture Groups are effective (Binnie and Allen 2008;Swain 2000a, 2000b;Cooper, Arnold, and Boyd 2001;Cooper and Lovey 1999;Cooper and Tiknaz 2005;Cooper and Whitebread 2007;Gerrard 2006;Iszatt and Wasilewska 1997;Lee and Scott 2009;O'Connor and Colwell 2002;Reynolds, MacKay and Kearney 2009;Sanders 2007;Seth-Smith et al 2010). This evidence base indicates that Nurture Groups can have significant positive impact on a child's SEBD, and have an impact on the acquisition of basic skills such as literacy.…”
Section: Evidence Base For Secondary School Nurture Groupsmentioning
confidence: 95%
“…There is now a sizeable evidence base that indicates that primary school Nurture Groups are effective (Binnie and Allen 2008;Swain 2000a, 2000b;Cooper, Arnold, and Boyd 2001;Cooper and Lovey 1999;Cooper and Tiknaz 2005;Cooper and Whitebread 2007;Gerrard 2006;Iszatt and Wasilewska 1997;Lee and Scott 2009;O'Connor and Colwell 2002;Reynolds, MacKay and Kearney 2009;Sanders 2007;Seth-Smith et al 2010). This evidence base indicates that Nurture Groups can have significant positive impact on a child's SEBD, and have an impact on the acquisition of basic skills such as literacy.…”
Section: Evidence Base For Secondary School Nurture Groupsmentioning
confidence: 95%
“…The majority of the studies (n = 11) focused on NGs set up in infant and primary schools (Bani 2011;Binnie and Allen 2008;Colwell and O'Connor 2003;Cooper, Arnold, and Boyd 2001;Cooper and Whitebread 2007;Doyle 2005;O'Connor and Colwell 2002;Reynolds, MacKay, and Kearney 2009;Sanders 2007;Scott and Lee 2009;Seth-Smith et al 2010). One study reported on a NG adapted for secondary school children in years 7 and 8 (Cooke, Yeomans, and Parkes 2008), whilst another included findings from one secondary school (Cooper and Whitebread 2007).…”
Section: Age Groupmentioning
confidence: 98%
“…Seven out of the 11 effectiveness studies recruited control groups (Cooper, Arnold, and Boyd 2001;Cooper and Whitebread 2007;Gerrard 2005;Reynolds, MacKay, and Kearney 2009;Sanders 2007;Scott and Lee 2009;Seth-Smith et al 2010), 6 of which were matched to some extent (Cooper, Arnold, and Boyd 2001;Cooper and Whitebread 2007;Reynolds, MacKay, and Kearney 2009;Sanders 2007;Scott and Lee 2009;SethSmith et al 2010). Reynolds, MacKay, and Kearney (2009) The time between pre and post scores varied from three months (Doyle 2005) to one year (Cooke, Yeomans, and Parkes 2008;Cooper, Arnold, and Boyd 2001). However, one study (O'Connor and Colwell 2002) provided follow-up data for 12 of the children who had attended an NG, at a mean of 2.67 years since leaving the NG.…”
Section: Designmentioning
confidence: 98%
See 2 more Smart Citations